Sistem Informasi Kesatuan Kodim 0615 kuningan - Erlan Darmawan; Fahmi Yusuf; Anto Lospiyanto (NUANSA INFORMATIKA, 2011)
Komando Distrik Militer (Kodim) is a supervising and operational commando in militery departmen under Komando RayonMiliter (Koramil).Kodim 0615 Kuningan has not used information technology (software) in processing data, so that there are some data that is not arranged well. By using information technology, it can solve the problems effectively. Information system used in Â Kodim 0615 Kuningan is made to solve the problem in processing data so it can save the time and financial side. The data information system is integrated well and it can reduce the mistake of data manipulation than manual way.Keywords : data, information, system,